2006
DOI: 10.1007/s11255-006-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between serum magnesium and parathyroid hormone in peritoneal dialysis patients: a contributing factor to adynamic bone disease?

Abstract: Serum Mg is lower and serum PTH higher in patients dialyzed with lower Mg concentration dialysis solution compared to those with higher Mg concentration dialysis solution. Our study confirms previous reports that serum Mg may have a suppressive role on PTH synthesis and/or secretion, and thus may play a role in pathogenesis of adynamic bone disease that often develops in patients on chronic PD with high calcium and high magnesium concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
4
21
1
Order By: Relevance
“…Therefore, these experiments show for the first time on the molecular level how Mg 2ϩ influences renal P i excretion. Moreover, these data also confirm previous findings that Mg 2ϩ influences PTH secretion not only in vitro but also in vivo (2,5,10,16,23,26,33).…”
Section: F1131supporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, these experiments show for the first time on the molecular level how Mg 2ϩ influences renal P i excretion. Moreover, these data also confirm previous findings that Mg 2ϩ influences PTH secretion not only in vitro but also in vivo (2,5,10,16,23,26,33).…”
Section: F1131supporting
confidence: 90%
“…In peritoneal dialysis patients, serum Mg 2ϩ concentration is inversely correlated with PTH levels (23,33). Taken together, these observations point to an influence of Mg 2ϩ on PTH secretion in vivo.…”
mentioning
confidence: 77%
“…The calcium-sensing receptor in the parathyroid glands is affected by magnesium, and both hypermagnesemia and severe hypomagnesemia can suppress PTH [28,29,30,31,32]. In dialysis patients, many studies have shown an association between lower dialysate [14,33,34,35] or serum [17,36,37] magnesium and higher PTH. However, similar to our findings, Cho et al [38] and O'Donovan et al [39] also failed to show any association between dialysate magnesium and PTH.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, unlike other reports, we found that there was no inverse relationship between serum Mg and PTH. 18,[39][40][41] One of the reasons for the difference might be sample differentia. The patients who are included had severe secondary hyperparathyroidism with PTH4500 pg/mL and unmanageable parathyroid hyperplasia.…”
Section: Discussionmentioning
confidence: 99%